2018
DOI: 10.1073/pnas.1807962115
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal behavioral, cellular, and molecular changes in models of Huntington disease are reversible by HDAC inhibition

Abstract: SignificanceIn Huntington disease (HD) gene carriers the disease-causing mutant Huntingtin (mHTT) is already present during early developmental stages, but, surprisingly, HD patients develop clinical symptoms only many years later. While a developmental role of Huntingtin has been described, so far new therapeutic approaches targeting those early neurodevelopmental processes are lacking. Here, we show that behavioral, cellular, and molecular changes associated with mHTT in the postnatal period of genetic anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 92 publications
(119 reference statements)
1
48
0
Order By: Relevance
“…Furthermore, genetic mutation or knockdown of Hdac2 in the central nervous system improved spatial, associative, and threat recognition memory in mouse models of Pitt-Hopkins syndrome (Tcf4 +/-) (17) and Alzheimer's disease (CK-p25) (18,19). Encouragingly, small molecule HDAC inhibitors conferred cognitive benefits in rodent models of aging (20,21), neurodegeneration (6,(21)(22)(23)(24)(25)(26), and neuropsychiatric (27)(28)(29)(30)(31)(32)(33)(34) disease. Taken together with observations of aberrant HDAC levels in postmortem human brain tissue from donors with Alzheimer's disease (18,19,35), SCZ (29,(36)(37)(38)(39)(40), depression (28,37), and bipolar disorder (39), these findings suggest that HDAC-related mechanisms may play a fundamental role in human cognition.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, genetic mutation or knockdown of Hdac2 in the central nervous system improved spatial, associative, and threat recognition memory in mouse models of Pitt-Hopkins syndrome (Tcf4 +/-) (17) and Alzheimer's disease (CK-p25) (18,19). Encouragingly, small molecule HDAC inhibitors conferred cognitive benefits in rodent models of aging (20,21), neurodegeneration (6,(21)(22)(23)(24)(25)(26), and neuropsychiatric (27)(28)(29)(30)(31)(32)(33)(34) disease. Taken together with observations of aberrant HDAC levels in postmortem human brain tissue from donors with Alzheimer's disease (18,19,35), SCZ (29,(36)(37)(38)(39)(40), depression (28,37), and bipolar disorder (39), these findings suggest that HDAC-related mechanisms may play a fundamental role in human cognition.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that HDAC3 was a class I histone deacetylase [39]. Histone deacetylase inhibition has a neuro-protective effect via reducing neuroinflammation [33], reported to be beneficial with respect to neurological functions in many diseases, including Alzheimer's disease [40], Huntington's disease [41], TBI, stroke [42], and spinal cord injury [33]. Recent studies reported that HDCA3 inhibition appears to suppress NF-κB transcriptional activity by maintaining the NF-κB p65 acetylated (inactive) state and restraining the inflammatory response [33,43].…”
Section: Discussionmentioning
confidence: 99%
“…We show that Nmnat can improve behavioral and survival phenotypes in HD even when induced at advanced disease stages. This will be clinically beneficial, as most therapeutic interventions are only effective in premanifest disease stages of HD when mild symptoms may be reversible, whereas disease progression becomes faster and relatively resistant to treatment when the symptoms have been fully developed (72). The observed reduction of NMNAT transcript level detected in human HD brains, typically in the caudate nucleus region (73), indicates that compromised Nmnat function may correlate with increased susceptibility to HD.…”
Section: Discussionmentioning
confidence: 99%